(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The effects of the Covid 19 pandemic on higher education in South Africa and the University of Pretoria iinspired this brief investigation into how the university responded to the Spanish Flu epidemic of 1918. This article looks at some of the traces of the effects of the Spanish Flu found in the University of Pretoria Archives. These include, apart from official documents, a handful of student reminiscences of the times which give some insights into how students in particular experienced the epidemic. These will be contrasted to personal impressions of how Covid 19 has impacted the 2020 class at the University of Pretoria. This brief comparison points to the far reaching impact the current pandemic has had on the university and higher education more generally.